Meningkatkan Kemampuan Menghindari Diri Dari Bahaya Listrik Melalui Metode Demonstrasi Pada Pembelajaran Bina Diri Bagi Anak Tunagrahita Sedang - Dasmi - - (Jurnal Penelitian Pendidikan Khusus, 2014)
This Research was conducted based on field findings in class VII C1 of SMP-LB AL-Hidayah Padang, there were two middle mentally disabled students namely MS and MY.They still couldn’t keep themselves from electric danger well. Self avoiding ability is a part of self treatment lesson.In order to ease learning for children in this research, tehe research used demonstration method, as demonstration  method could make the learning more concrete, so that the learning process would be more interesting. This research was conducted by using classroom action research method and collaborated wit a peer.Research findings showed that 1) the pocess in increasing self avoiding ability of electric danger through demonstration method was done with two cycle. Cycle 1 was in order the students are able to use electric appliances well well in which done four times of meeting.2) the learning result of self avoiding ability of electric danger through demonstration method was the student”sability when MS’s assessment was 7,14 % whereas MY”s was 14,28 %. After the learning was given on cycle 1 through demonstration method, MSs self avoiding ability of electric danger was (50%) and MY’s was (66,6%). On cycle 11,   they learned self avoiding ability of electric danger through demonstration method. The result found that MS’s ability was (62,5%) and MY’s WAS (75%). Thus, it can be concluded that demonstration method could increase the middle mentally disabled student’s ability in avoiding electric danger of class VII C1 in SLB AL- Hidayah Padang.